Mental illness stigma: a case of Ingutsheni Hospital’s outpatients - Nkomo, Gift (Midlands State University, 2015)
Mental illness has been in existence for some centuries but ironically, the levels of stigma attached to it were still unbelievably high. In most cases as soon as a person was given a diagnosis of any mental condition they earned themselves discriminatory names from the general public (Corrigan, 2004). The stigma of mental illness, although more often related to context than to person’s experience, remained a powerful negative attribute in all social relations. The stigmatization of mental illness was a serious problem affecting patients and their relatives as well as institutions and healthcare personnel working with people with mental illness.